Frequent KRAS and HRAS mutations in squamous cell papillomas of the head and neck - Eiichi Sasaki; Katsuhiro Masago; Shiro Fujita; Nobuhiro Hanai; Yasushi Yatabe (Wiley, 2020)
Abstract Squamous cell papilloma (SCP) is a benign neoplasm of the head and neck. Human papillomavirus (HPV) has been reported to be a tumourigenic factor for SCP. However, not all SCPs are positive for HPV, suggesting that other possible mechanisms are involved in their development. In this study, we examined the mutational status of 51 SCPs using targeted panel sequencing in addition to HPV status using GP5+/GP6+ PCR. HPV DNA was detected in 6 (12%) SCPs, while KRAS and HRAS mutations were detected in 18 (35%) and 17 (33%) SCPs, respectively. Notably, KRAS mutations, HRAS mutations and HPV infection were mutually exclusive. The larynx and trachea (4/7, 57%) were more preferentially infected by HPV than the other sites (2/44, 5%, p = 0.0019) and HPV was associated with multifocal development (4/5, 80%). In contrast, KRAS and HRAS mutations in SCPs were evenly distributed across the anatomical sites and found only in single SCPs. In conclusion, this study demonstrated that HPV was not frequently involved in SCPs and that RAS mutations were more common alterations. In contrast to inverted sinonasal papillomas and oncocytic sinonasal papillomas, SCP may not be a precursor lesion of carcinoma, because these aetiological events in SCP are distinct from squamous cell carcinoma in the same sites.